2010
DOI: 10.1007/s00216-009-3437-x
|View full text |Cite
|
Sign up to set email alerts
|

Screen-printed sensor for batch and flow injection potentiometric chromium(VI) monitoring

Abstract: A disposable screen-printed electrode was designed and evaluated for direct detection of chromium(VI) in batch and flow analysis. The carbon screen-printed electrode was modified with a graphite-epoxy composite. The optimal graphite-epoxy matrix contains 37.5% graphite powder, 12.5% diphenylcarbohydrazide, a selective compound for chromium(VI), and 50% epoxy resin. The principal analytical parameters of the potentiometric response in batch and flow analysis were optimized and calculated. The screen-printed sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In addition, the amount of graphite in the composite matrix must be optimized to obtain stable materials which present good mechanical properties and electrical conductance. Following the results obtained in previous works 11, 12 and in order to obtain the maximum electrical conductance without loss of stability and hardness of the cured material and the best potentiometric response of the bisensor, the graphite‐epoxy composites were prepared in both cases with 50 % (w/w) epoxy resin, 37.5 % (w/w) graphite powder and 12.5 % (w/w) DPC or DPHE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the amount of graphite in the composite matrix must be optimized to obtain stable materials which present good mechanical properties and electrical conductance. Following the results obtained in previous works 11, 12 and in order to obtain the maximum electrical conductance without loss of stability and hardness of the cured material and the best potentiometric response of the bisensor, the graphite‐epoxy composites were prepared in both cases with 50 % (w/w) epoxy resin, 37.5 % (w/w) graphite powder and 12.5 % (w/w) DPC or DPHE.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of pH on the potentiometric response for screen‐printed sensors modified with graphite‐epoxy composites containing DPC has been studied 12. The results showed that the pH dependence of the sensor in presence and in absence of chromium(VI) solution is probably due to the nature of the graphite‐epoxy composite matrix.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the limits fixed by the Water Framework Directive [3] for four heavy metals, i.e., lead, cadmium, mercury and nickel, it appears that research on ISEs has been largely focused on lead at the required nano-molar level [77,81], and potentiometric detection at these levels for other important toxic ions, e.g., manganese and arsenate, has so far not been reported [93] or it is below the environmental policy requirements, e.g., Cr(VI) [94]. In this regard it is worthwhile to note that the measurement of cadmium at 1 ppb levels, i.e., compatible with some water regulation policies, in concentrated NaCl samples (simulating sea water) with ISE was reported [95].…”
Section: Recent Advances In Solid-contact Ion-selective Electrodes (Smentioning
confidence: 99%